1972
DOI: 10.1017/s002185960002640x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of disease on the oestrogenic activity and coumestrol content of white clover and lucerne

Abstract: SUMMARYThe oestrogenic activity and coumestrol content of ‘diseased’ and ‘clean’ white clover and lucerne were investigated. It was found that both coumestrol content and oestrogenic activity were increased in diseased white clover. However, there was insufficient coumestrol to account for the oestrogenic activity and it was suggested that other factors (e. g. oestrogen potentiator, unidentified oestrogen) were involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Coumestrol [syn 7'12' dihydroxy coumestan] has been found in 58 plants [2], especially legumes, (e.g., lucerne), other perennial Medicago (e.g., M. falcata), annual 'medics' (Medicago spp. ), peas (Pisum sativum), soybean, limabeans (Phaseolus lunatus), pinto beans (P. vulgaris), and some clovers (e.g., white clover [5,19,20] and strawberry clover (T. fragiferum) [6]). The relative abundance of particular coumestans and flavones that white clover produces in the field varies considerably depending on which plant pathogen stimulates their production [21,22].…”
Section: Phytoestrogenic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coumestrol [syn 7'12' dihydroxy coumestan] has been found in 58 plants [2], especially legumes, (e.g., lucerne), other perennial Medicago (e.g., M. falcata), annual 'medics' (Medicago spp. ), peas (Pisum sativum), soybean, limabeans (Phaseolus lunatus), pinto beans (P. vulgaris), and some clovers (e.g., white clover [5,19,20] and strawberry clover (T. fragiferum) [6]). The relative abundance of particular coumestans and flavones that white clover produces in the field varies considerably depending on which plant pathogen stimulates their production [21,22].…”
Section: Phytoestrogenic Compoundsmentioning
confidence: 99%
“…The relative abundance of particular coumestans and flavones that white clover produces in the field varies considerably depending on which plant pathogen stimulates their production [21,22]. The coumestrol content in white clover was considered insufficient to explain the oestrogenic activity it was responsible for [5,20] 4'-methoxy-coumestrol is considered the second most important coumestan for oestrogenic activity. In annual medics it is usually detected in amounts somewhat greater than coumestrol, viz.…”
Section: Phytoestrogenic Compoundsmentioning
confidence: 99%
“…It is now well established that the oestrogenic activity of subterranean and red clovers is due to the presence of high concentrations of the weakly oestrogenic isoflavones, and more specifically it has been shown that for sheep the oestrogenicity of these pastures is related to their formononetin content. Early investigations on the oestrogenic activity of white clover (Trijolium repens) were inconclusive; however, more recent studies have shown that white clover infected with Pseudopeziza trifolii or Leptosphaerulina trifolii may become highly oestrogenic (Newton et al 1969;Wong, Flux & Latch, 1971;Saba et al 1972) thus offering a possible explanation for the variable results of earlier studies. In view of these findings it was of some interest to determine seasonal variation in oestrogenic activity of white clover pastures.…”
Section: Introductionmentioning
confidence: 99%
“…Coumestrol content within alfalfa herbage is highly variable and ranges from less than 1 mg kg -1 DM to 600 mg kg -1 DM in diseased foliage (Hanson et al, 1965;Saba et al, 1972). Coumestrol contents as low as 25 mg kg -1 DM have been demonstrated to affect ewe reproductive performance (Fields et al, in press;Ramòn et al, 1993;Smith et al, 1979).…”
mentioning
confidence: 99%
“…Fungal disease is considered the main factor that elevates coumestrol content and all fungal pathogens tested to date have increased coumestrol (Bickoff et al, 1967;Hanson et al, 1965;Saba et al, 1972;Sherwood et al, 1970 , (1906)]. Fungicide applications of mancozeb or mancozeb and benomyl every 7 to 10 d could limit coumestrol accumulation (Hanson et al, 1965;Purves et al, 1981).…”
mentioning
confidence: 99%